Investigating increasing the level of learning and making students interested in mathematics - Tashbaevich Nurmanov , Abdinazar; Javohir Gaybullo Ugli , Zokirov; Suluv Khurramovna , Sullieva; Zebiniso, Kabilova; Sevara, Primkulova; Kurbonalijon Gaybullo Ugli, Zokirov (Cadernos de Educação Tecnologia e Sociedade, 2024)
The research in question is the lack of interest, inattention, and passivity of students in carrying out mathematics activities and the unsatisfactory results of the tests. The purpose of this research was to increase the level of interest of students in mathematics and create motivation and interest in mathematics. The article is a method analysis type and to collect the contents of this research, school experiences and also a review of previous research were used. It is no secret to any of the mathematics activists in the field of education that many students are not interested in mathematics and have problems learning it. In this regard, this research has presented methods for creating motivation in learning mathematics based on the experiences of different schools. By conducting this research, I first identified the causes of students' lack of interest in mathematics and then, by benefiting from the points of view of teachers and parents, books and magazines, experiences, and innovative ways, increased students' interest in mathematics. For this purpose, by using various and modern teaching methods such as brainstorming, games and mathematics, making teaching aids, as well as implementing projects such as "I Can Do It" projects, "Idea from You" and "A Day in the Hands of Children" and using descriptive evaluation to solve group problems, student participation in the class was increased, and by creating a happy and friendly environment, the feeling of fatigue and monotony in the classroom was eliminated and the desired learning situation was provided. The results showed that accurately identifying the cause of lack of interest in mathematics and providing a combination of the above solutions made students interested in learning mathematical concepts. In the end, it was concluded that using various teaching methods, appropriate to the purpose of each lesson, providing functional activities to students according to individual differences, students' needs and interests and appropriate encouragement, strengthening visual and auditory memory, and cultivating learners' accuracy and attention in the form of purposeful games, has been very effective in increasing students' interest in mathematics and performing their functional activities.